Building Leader Power and Team Loyalty Leadership and the Art of Followership in an Islamic Perspective - Salamun, Ade (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2025)
Islam emphasizes how a leader should act and how a good follower can support effective leadership. This article reviews how leadership and followership are intertwined and how Islamic values guide the carrying out of both roles. This article uses a qualitative method with a descriptive and literature study approach. The Prophet Muhammad SAW exemplified how leadership should prioritize trustworthiness, responsibility, justice, wisdom, perseverance, and empathy. An ideal leader in Islam does not only focus on power but also integrity and balance between worldly and hereafter interests. In addition, a good follower of Islam must have obedience with understanding, healthy loyalty, and the ability to provide constructive input. One example of effective interaction between leaders and followers is seen in Islamic history, such as in the Battle of Khandaq, when Salman Al-Farisi proposed a trench-digging strategy accepted wholeheartedly by the Prophet Muhammad PBUH. Leadership success in Islam depends on a harmonious relationship between leaders and followers, where both parties support each other and build a shared vision.